Green Stimulus in a Post-Pandemic Recovery: The Role of Skills for a Resilient Recovery - Ziqiao Chen; Giovanni Marin; David Popp; Francesco Vona (Center for Economic Studies and Ifo Institute (CESifo), 2020)
As nations struggle to restart their economy after Covid-19 lockdowns, calls to include green investments in a pandemic-related stimulus are growing. Yet little research provides evidence of the effectiveness of a green stimulus. We begin by summarizing recent research on the effectiveness of the green portion of the 2009 American Recovery and Reinvestment Act on employment growth. Green investments are most effective in communities whose workers have the appropriate “green” skills. We then provide new evidence on the skills requirements of both green and brown occupations, as well as from occupations at risk of job losses due to Covid-19, to illustrate which workers are most likely to benefit from a pandemic-related green stimulus. We find similarities between some energy sector workers and green jobs, but a poor match between green jobs and occupations at risk due to Covid-19. Finally, we provide suggestive evidence on the potential for job training programs to help ease the transition to a green economy.
Keywords: E24; E62; H54; H72; Q58; 330; green subsidies; green stimulus; American Recovery Act; heterogeneous effect; distributional impacts